Evaluation Of The Kotaku Program (City Without Slums) (Study In Biringkanaya District, Makassar City) - To Taddampali, Andi Caezar; Siraj, Muhammad Luthfi; S, Muh Rizal (Universitas Negeri Makassar, 2022)
This study aims to determine the evaluation of the implementation of the City Without Slums Program (KOTAKU) in Biringkanaya District, Makassar City, and the impact of the implementation of the Slumless City Program (KOTAKU) in Biringkanaya District, Makassar City. This research uses a qualitative research type with a descriptive approach. Data collection techniques were carried out using observation, interviews, and documentation. The data analysis technique in this study used an analytical model according to Spradley. The results of this study indicate that the implementation of the KOTAKU (City Without Slums) Program Evaluation (Study at Biringkanaya District, Makassar City) is not well implemented according to the concept of Edward a Suchman. Indicators that do not work well are: a. program objectives, b. problem analysis, c. measurement of change, d. changes to the consequences of activities, e. program impact. The indicators that run well are description and standardization. The impact of the City Without Slums Program (KOTAKU) is that not all people can feel the infrastructure development in Biringkanaya sub-district. The lack of community participation in maintaining infrastructure has led to the less successful Cities Without Slums (KOTAKU) Program.